أثر شكل أربطة الإطارات البيتونية المسلحة للأبنية العالية على القوى المتولدة في عناصر الإطار - طريفي زكائي (Latakia University Journal -Engineering Sciences Series, 2016)
نظرا لكون الإطارات البيتونية تخضع لانتقالات جانبية كبيرة وخصوصاً في حالة المباني العالية، حيث يصعب تخفيض الإزاحات فإنه من المفيد تحسين سلوكها لتخفيض الانتقالات الجانبية وذلك من خلال الأربطة. يمكن استخدام الأربطة أيضا في حالات تدعيم وزيادة كفاءة الأبنية البيتونية القائمة. تتنوع أشكال أربطة الإطارات البيتونية بهدف تحقيق فتحات النوافذ والأبواب في جدران الإطارات. يهدف البحث إعطاء فكرة للمصمم عن أثر شكل الأربطة في قوى المقطع المتولدة في عناصر الإطارات البيتونية المسلحة للأبنية العالية . أجريت الدراسة على إطار من البيتون المسلح مؤلف من خمس فتحات وبارتفاع خمسة عشر طابقاً. تمت مقارنة أشكال مختلفة من الأربطة المعدنية وهي بشكل X ، V ، K و O . أجريت الحسابات بالاعتماد على برنامج CSI-SAP 2000 . أجريت مقارنة قيم الانتقالات الطابقية للإطار البيتوني بالعلاقة مع أشكال الأربطة، وتبين بأن للأربطة فعالية كبيرة في تخفيض الانتقالات الطابقية، ففي حالة الأربطة بشكل X و V انخفضت قيم الانتقالات في الطابق الأخير بنسبة 52.38 % ، أما في حالة الأربطة بشكل K و O فقد انخفضت قيم الانتقالات الطابقية بنسبة 23.07 % . أجريت مقارنة مفصلة لقيم قوى المقطع أي العزوم وقوى القص والقوى الناظمية في جوائز وأعمدة الإطار البيتوني في الطابقين الأول والثاني بالعلاقة مع أشكال الأربطة. تم الاستنتاج بأن للأربطة بشكل X و V فعالية كبيرة لإطارات الأبنية البيتونية العالية، وكذلك لحالات رفع كفاءة الأبنية البيتونية الإطارية القائمة . Due to the sensitivity of concrete frames to the lateral displacement especially in the case of tall buildings, it is useful to improve the behavior to resistance the lateral displacement through bracing. Bracing can be used in cases of rehabilitation and increasing the efficiency of existing concrete buildings. Varied shapes of bracing for concrete frames in order to achieve opening for windows and doors in the wall of frames. The research aims to give an idea for designer on the effect of the shape of bracing on the cross section forces generated in the elements of R/C tall buildings frame elements. The Study was conducted on R/C frame which consist from five spans, and fifteen storeys. It has compared different shapes of metal bracing, which are X, V, K and O. Calculation were based on Program CSI-SAP 2000. Conducted compared for the storylateral displacement of concrete frame in relation with the bracing shape. It shows that the bracing have large effect to reduce the storey lateral displacement, in the case of the bracing with X and V shape decreased the value of displacement in the last story in ratio 52.38%, in the case of bracing with K and O shape decreased in ratio 23.07%. Conducted detailed comparison for the value of cross section i.e. Moments, shear and axial forces in beams and columns of first and second floor frame in relationship of bracing shape. It concludes thatX and V bracing have large effect on the concrete tall buildings frame, as well as in the cases of improving the efficiency of existing R/C frame buildings.